PENGARUH PROGRAM GERAKAN LITERASI SEKOLAH (GLS) TERHADAP KEBIASAAN MEMBACA SISWA KELAS V SEKOLAH DASAR - Yudiana, Meigita; Dafit, Febrina (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study is motivated by Indonesia’s low reading literacy ranking in PISA 2018 (72nd out of 78 countries) and the lack of quantitative evidence regarding the effectiveness of the stages of the School Literacy Movement (GLS) in public elementary schools. The aim is to analyze the extent to which the implementation of GLS is associated with the reading habits of fifth-grade students at SDN 163 Pekanbaru. The research employed a quantitative approach with a correlational ex post facto design. The population consisted of all fifth-grade students (n = 103), with a purposive sample of 34 students from class VA. Data were collected using GLS program questionnaires (three stages: habituation, development, and learning) and reading habit questionnaires (frequency, duration, sources, and book collections), which had been content-validated by two experts (CVI = 0.92) and proven reliable (? = 0.815–0.821). Simple linear regression analysis revealed that GLS contributed significantly to reading habits (p = 0.001) with R² = 0.278 (effect size f² ? 0.385, medium–large). These findings underscore the need to strengthen GLS implementation structurally by enhancing the quality of activities in the development and learning stages, increasing the variety of reading materials, and ensuring continuous teacher mentoring. The results provide a basis for school and local government policies to design more measurable and sustainable literacy interventions at the elementary school level. ABSTRAK Penelitian ini dilatarbelakangi rendahnya peringkat literasi membaca Indonesia pada PISA 2018 (urutan ke-72 dari 78 negara) dan kurangnya bukti kuantitatif terkait efektivitas tahapan Gerakan Literasi Sekolah (GLS) di sekolah dasar negeri. Tujuan penelitian adalah menganalisis sejauh mana pelaksanaan GLS berasosiasi dengan kebiasaan membaca siswa kelas V di SDN 163 Pekanbaru. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional ex post facto. Populasi penelitian adalah seluruh siswa kelas V (n = 103), dan sampel 34 siswa kelas VA dipilih secara purposive. Data dikumpulkan menggunakan angket program GLS (tiga tahap: pembiasaan, pengembangan, pembelajaran) dan angket kebiasaan membaca (frekuensi, durasi, sumber, koleksi bacaan) yang telah divalidasi isi oleh dua ahli (CVI = 0,92) dan reliabel (? = 0,815–0,821). Analisis regresi linear sederhana menunjukkan GLS berkontribusi signifikan terhadap kebiasaan membaca (p = 0,001) dengan R² = 0,278 (kategori efek f² ? 0,385, sedang–besar). Temuan ini menegaskan perlunya penguatan implementasi GLS secara struktural melalui peningkatan kualitas kegiatan pada tahap pengembangan dan pembelajaran, penambahan ragam bahan bacaan, serta pendampingan guru yang berkelanjutan. Hasil penelitian dapat menjadi dasar kebijakan sekolah dan pemerintah daerah untuk merancang intervensi literasi yang lebih terukur dan berkelanjutan di tingkat sekolah dasar.